Desain Controller Pada Heating Furnace Berbasis Metode Firefly Algorithm (FA) - Febrian Rizal Anas; Dwi Ajiatmo; Hidayatul Nurohmah; Ali, Machrus (Universitas Darul Ulum, 2022)
Furnace is an equipment used to heat or change shape. Process control has become increasingly important in industry, as a consequence of global competition, Year after year, furnaces have improved in both process and industrial equipment. The tuning process ensures that system performance meets operating objectives. Artificial Intelligent (AI)-based intelligent control has developed a lot to improve conventional controls to control voltage loads and is always under constant assessment of the variable. In this research task, it will be discussed about the control of the furnace temperature so that it remains constant with PID and by tuning the Firefly Algorithm (FA) with changes in the output voltage obtained which have better settling time, overshoot and undershoot.